Assessment of Heavy Metal Contamination in the Diwaniyah River: Tracing Industrial and Municipal Effluent Sources - Bhatkar, Prajwalkumar; Agrawal, Amit Kumar (Journal of Research in Science and Engineering, 2026)
This study investigates the contamination of heavy metals in the Diwaniyah River due to industrial and sewage discharge. The levels of lead (Pb), cadmium (Cd), zinc (Zn), and chromium (Cr) were analyzed to determine the extent of pollution. The study found that zinc recorded the highest concentration at 0.1141 mg/L, followed by chromium (0.0508 mg/L), lead (0.0244 mg/L), and cadmium (0.0117 mg/L). Statistical analysis using SPSS revealed that Al - Hamza Al - Sharqi District exhibited the highest levels of contamination. The findings highlight the urgent need for pollution control measures to mitigate heavy metal accumulation in water sources.